Chilling times: social media policies, labour law and employment relations - Thornthwaite, Louise (Asia Pacific journal of human resources, 2016)
The increasing pervasiveness of web‐based technologies presents employers with particular challenges in terms of employee voice and resistance, as well as surveillance, privacy and discipline. This paper is concerned with the implications for human resource management and labour law of the social media policies with which employers increasingly regulate employee online behaviour when off‐duty. The object is to consider in particular the content of employers' social media policies in relation to expression of employee voice, and the limits which national labour laws might impose. Employment laws in Australia and the United States are compared. Through focusing on the implications of social media policies for the regulation of employees' online behaviour outside the workplace, this paper is concerned also with the purpose and scope of employment law and human resource policy, particularly in relation to employees' private lives and, by association, the scope of employees' implied contractual duties. Key points This article explores the implications of social media policies for the regulation of employee behaviour outside work. Social media policies involve a critical intersection between HRM policy and employment law. This qualitative case study demonstrates the potential chilling effect of social media policies on employee voice and expression in their personal lives.